Emotional demands at work and risk of long-term sickness absence in 1·5 million employees in Denmark: a prospective cohort study on effect modifiers - Elisabeth Framke, PhD; Jeppe Karl Sørensen, MSc; Kristina Alexanderson, ProfPhD; Kristin Farrants, PhD; Mika Kivimäki, ProfFMedSci; Solja T Nyberg, PhD; Jacob Pedersen, PhD; Ida E H Madsen, PhD; Reiner Rugulies, ProfPhD (Elsevier, 2021)
Summary: Background: High emotional demands at work can affect employees' health and there is a need to understand whether such an association might be modified by other working conditions. We aimed to examine emotional demands at work as a risk factor for long-term sickness absence and analyse whether influence, possibilities for development, role conflicts, and physical demands at work might modify this risk. Methods: We did a nationwide, population-based, prospective cohort study in Denmark and included employed individuals who were residing in Denmark in 2000, aged 30-59 years, who had complete data on age, sex, and migration background, with information on emotional demands and possible effect modifiers from job exposure matrices, and covariates and outcome (sickness absence) from population registers. Individuals with long-term sickness absence (≥6 weeks of consecutive sickness absence) between Jan 1, 1998, and Dec 31, 2000, and self-employed individuals were excluded. We assessed long-term sickness absence during a 10-year period from Jan 1, 2001, to Dec 31, 2010. Using Cox regression, we estimated hazard ratios (HRs) and 95% CIs and tested interaction as departure from additivity, estimating relative excess risk due to interaction (RERI). Multivariable adjusted models included sex, age, cohabitation, migration background, and income. Findings: 1 521 352 employed individuals were included and contributed data between Jan 1, 2000, and Dec 31, 2010. During 11 919 021 person-years (mean follow-up 7·8 years), we identified 480 685 new cases of long-term sickness absence. High emotional demands were associated with increased risk of long-term sickness absence compared with low emotional demands, after adjusting for age, sex, cohabitation, migration background, income, and the four possible effect modifiers (adjusted HR 1·55 [95% CI 1·53-1·56]). The association between high emotional demands and risk of long-term sickness absence was stronger in a synergistic way when individuals were also exposed to low possibilities for development (RERI 0·35 [95% CI 0·22-0·47]; 28·9 additional cases per 1000 person-years) and high role conflicts (0·13 [0·11-0·15]; 22·0 additional cases per 1000 person-years). No synergy was observed for influence and physical demands at work. Interpretation: People in occupations with high emotional demands were at increased risk of long-term sickness absence. Our findings on synergistic interactions suggest that, in emotionally demanding occupations, increasing possibilities for development and reducing work-related role conflicts might reduce long-term sickness absence. Further interventional studies are needed to confirm or refute this hypothesis. Funding: Danish Work Environment Research Fund, NordForsk.